Hypothyroidism correlates with dyslipidemia and protein contents in patients with various metabolic disorders. Issue 9 (September 2022) - Kiran, Muniba; Ejaz, Samina; Iqbal, Muhamad Nouman; Malik, Waqas Nazir; Zahoor, Sana; Ejaz, Syeda Abida
Objectives: The present study aimed to investigate the status of abnormalities in thyroid-related hormones, lipid profile parameters and total proteins in the sera of patients suffering from various metabolic disorders. Methods: To analyze the study parameters, enzyme-linked immunosorbent assays, Bradford assays and standard clinical kits and methods were applied. Data were analyzed through the appropriate statistical tests. Results: In all subjects except those with hypotension, thyroid-stimulating hormone, total cholesterol and low-density lipoprotein were elevated, whereas triiodothyronine levels were downregulated. Thyroxin was downregulated in subjects with diabetes and symptomatic thyroiditis but upregulated in patients with hypertension. High-density lipoprotein was upregulated in men who were diabetic only, and total protein was downregulated in those with hypotension only. Hypothyroidism in patients with diabetes, symptomatic thyroiditis and hypertension was correlated with dyslipidemia. In subjects with hypertension, it was correlated with total protein. Conclusion: This study revealed a link between hypothyroidism, dyslipidemia and total protein in patients with various metabolic disorders.